Pengaruh Masa Kerja, Lama Paparan Terhadap Gejala Gangguan Fungsi Paru Pada pekerja garment UD. Surabaya Kabupaten Jember (Studi di UD. Surabaya Kabupaten Jember) - Mayang Sari Eka Sriwahyuningsih; Ancah Caesarina Novi Marchianti; Hadi Prayitno (Pascasarjana Universitas Jember, 2020)
One of the vital organs in humans is the lungs. Disorders that occur in the lungs will make the body's metabolism unbalanced and can reduce the quality of the human body. Pulmonary function disorders do not only occur in developed countries but in developing countries such as Indonesia. Lung function disorders can be caused by occupations with high dust exposure such as the Garment Industry.The purpose of this study was to analyze the effect of work tenure, length of exposure to symptoms of lung function disorders in garment workers in UD Surabaya, Jember Regency. The data used are primary data obtained from questionnaires of 108 worker respondents. The analysis tool uses regression of weight techniques using AMOS software. The results of instrument testing conclude that all variables are valid and reliable as data collection tools. The results of data analysis indicate that: 1) tenure has a positive effect on symptoms of lung function disorders in garment workers. 2) the length of exposure has a positive effect on symptoms of lung function disorders in garment workers. 3) Most of UD garment workers. Surabaya, Jember Regency has or is experiencing symptoms of lung function disorders in the form of coughing and chest tightness / breathing. Keywords: Lung function disorders, working period, length of exposure.